Upregulation of amphiregulin by retinoic acid and Wnt signalling promotes liver cancer cell proliferation. Issue 2 (12th July 2019) - Lin, Hsuan‐Hwai; Peng, Yi‐Jen; Tsai, Ming‐Jiun; Wu, Yi‐Ying; Tsai, Tsung‐Neng; Huang, Hsin‐Hung; Shih, Yu‐Lueng; Chang, Wei‐Kuo; Hsieh, Tsai‐Yuan
Abstract: Activated hepatic stellate cells promote hepatocellular carcinoma (HCC) progression. Hepatic stellate cells play a key role in retinoid metabolism, and activation of stellate cells increases retinoic acid (RA) in the liver. However, the role of RA in HCC proliferation remains unclear. We aimed to analyse the mechanism of RA in HCC proliferation. Thirty‐eight patients who had undergone hepatic resection for HCCs were recruited. Paired non‐tumour tissues, adjacent and distal to HCCs, were collected, and the RA levels in the tissues were analysed. The mechanisms of RA and HCC proliferation were assessed in liver cancer cell lines by protein and gene expression analyses. Early recurrence of HCC was significantly higher in patients with a higher RA concentration than in those with a lower RA concentration in tissues adjacent to HCCs (61.1% vs. 20%, p  = .010). RA promoted HCC cell proliferation and activated the expression of Amphiregulin, a growth factor in hepatocarcinogenesis. The promoter of Amphiregulin contained the binding sites of the RA receptor, RXRα. Wnt signalling also activated the expression of Amphiregulin, and the RA and Wnt pathways acted synergistically to increase the expression of Amphiregulin. Furthermore, RXRα interacted with β‐catenin and then translocated to the nucleus to activate Amphiregulin. An increased RA concentration in the tissues adjacent to the tumour was associated with an early recurrence of HCC. RA activated the expression of Amphiregulin, and then promoted HCC proliferation, which might partly contribute to early recurrence of HCC after hepatic resection. Abstract : An increase in the concentration of retinoic acid (RA) in the microenvironment of hepatocellular carcinoma (HCC) is associated with a higher recurrence rate after the curative hepatic resection. Our work suggests that RA concentration could be used as a potential marker for early recurrence.